2010
DOI: 10.1111/j.1475-6773.2010.01216.x
|View full text |Cite
|
Sign up to set email alerts
|

Small Group Employer Participation in New Mexico's State Coverage Insurance Program: Lessons for Federal Reform

Abstract: Objective. To identify factors associated with small group employer participation in New Mexico's State Coverage Insurance (SCI) program. Data Sources. Telephone surveys of employers participating in SCI (N=269) and small employers who inquired about SCI (N=148) were fielded September 2008–January 2009. Study Design. Descriptive and multivariate analyses investigated differences between employer samples, including employer characteristics, concerns that applied to the business when deciding whether to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…This study extends the existing literature in several ways. While state health reform efforts are routinely evaluated, relatively few investigations examine state initiatives targeted specifically at reforming the small group market, particularly in recent years (Buchmueller & Jensen, 1997;Burke, 2008;Jensen & Morrisey, 1999;Sommers et al, 2010;Xirasagar, Stoskopf, Shrader, & Glover, 2004). Indeed, the dearth of research in this area is highlighted by one recent review, which in noting the lack of evaluation efforts observed that "the success or failure of many small group business insurance initiatives remains unknown" (Napel, Cohn, & Martinez-Vidal, 2009).…”
Section: New Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study extends the existing literature in several ways. While state health reform efforts are routinely evaluated, relatively few investigations examine state initiatives targeted specifically at reforming the small group market, particularly in recent years (Buchmueller & Jensen, 1997;Burke, 2008;Jensen & Morrisey, 1999;Sommers et al, 2010;Xirasagar, Stoskopf, Shrader, & Glover, 2004). Indeed, the dearth of research in this area is highlighted by one recent review, which in noting the lack of evaluation efforts observed that "the success or failure of many small group business insurance initiatives remains unknown" (Napel, Cohn, & Martinez-Vidal, 2009).…”
Section: New Contributionmentioning
confidence: 99%
“…Outside of a handful of studies, however, the implementation side of the small group health insurance reform equation has generally been ignored (Burke, 2008;Hall, 2000;Silow-Carroll, Waldman, & Meyer. 2001;Sommers et al, 2010). This is with respect to key implementation activities such as outreach and oversight.…”
Section: New Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small employers who inquired about SCI but who decided not to participate were significantly more likely to report affordability concerns than did participating employers. This finding highlights that the size of employer subsidies will impact whether the ACA's small employer tax credits will encourage employers to offer coverage (Sommers et al 2011). …”
mentioning
confidence: 99%